Reporte final del desarrollo de la DEEVi- (Infonavit, 2014)
The Passive House Planning Package (PHPP) is an integrated tool for energy balance calculations including all energy flows within the system boundary. The programme is based in large part on European an international norms and is a desing tool for buildings with very low energy demand.